Common Ownership in the U.S. Pharmaceutical Industry: A Network Analysis - Albert Banal-Esta\~nol; Melissa Newham; Jo Seldeslachts (The Antitrust Bulletin, 2021)
We investigate patterns in common ownership networks between firms that are active in the U.S. pharmaceutical industry for the period 2004–2014. Our main findings are that “brand firms”—that is, firms that have research and development capabilities and launch new drugs—exhibit relatively dense common ownership networks with each other that further increase significantly in density over time, whereas the network of “generic firms”—that is, firms that primarily specialize in developing and launching generic drugs—is much sparser and stays that way over the span of our sample. Finally, when considering the common ownership links between brands firms, on the one hand, and generic firms, on the other, we find that brand firms have become more connected to generic firms over time. We discuss the potential antitrust implications of these findings.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer bundesweiten Konsortiallizenz in der Nachfolge einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. – This publication is with permission of the rights owner freely accessible due to an consortial licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; Common ownership networks; Pharmaceutical companies; Competition; Innovation